Development and Evaluation of TYFIREQUAKE: A Virtual Reality Simulation for Disaster Preparedness of Children - Balahadia, Francis F.; Sayaman, Jomar V. (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – This study aims to develop and evaluate TYFIREQUAKE virtual reality simulation of fire, earthquake, and typhoon scenarios using Virtual Reality (VR) as an alternative training tool and application for increasing the level of disaster preparedness to be able to apply the safety and precautionary measures in emergencies. Methodology – The proponents applied the Rapid Application Development (RAD) model as a software development model and followed the different phases such as outlining the requirements, user designs and input, constructions, and finalization of the software. The study incorporates different software for creating virtual environments, layout designs of scenarios, characters, controllers, interactive elements, and AI non-player characters. The system developed the desired output and functionalities like presenting the Before, During, and After scenarios of each disaster with time monitoring and assessment Results – Moreover, it was evaluated using test cases such as functionality case testing, sharing test, installation, and load test, portability test, performance test, and system test wherein the system Passed all tests. In this study, the design for simulated training on the disaster was discovered to be capable of exposing a person to a disastrous environment without endangering the person immersed in the condition. Conclusions – This virtual training program for earthquakes, fire, typhoons, and tsunami/floods can be used without a cost or by spending a lot of money on deploying real-life trainers and equipment for physical drills. The results of this study suggest that a similar design for a larger community may be provided to local cities mandated by the government to propagate disaster awareness and emergency preparedness programs. Recommendations – It is suggested that the developed mobile application can be implemented in emergency response teams as a tool for disseminating awareness of disasters, especially to the children.  Additional features that can provide feedback, a database as a repository of data and information for crafting more insightful ideas in generating activities on disaster prevention.  Research Implications  – The TYFIREQUAKE mobile application could be an effective training tool for equipping children with sufficient knowledge and skills in responding to typhoons, fires, and earthquakes. They can learn the proper strategies for coping with disasters specifically in identifying the possible safe places, maximizing the available resources, and action plans for recovery before, during, and after the disasters.